1984
DOI: 10.1007/bf01654463
|View full text |Cite
|
Sign up to set email alerts
|

The accessory middle cerebral artery (AMCA). Diagnostic and therapeutic consequences

Abstract: The existence of the accessory middle cerebral artery (AMCA) is a rare anatomical variation with an estimated incidence of 0.31%. The embryological development of this artery is unknown. Three anatomical subtypes are described: in the type 1 variety the AMCA arises from the internal carotid artery; in the type 2, the AMCA originates from the proximal part of the anterior cerebral artery; in type 3, the AMCA arises from the distal part of the anterior cerebral artery. The use of endovascular techniques to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 4 publications
0
18
0
3
Order By: Relevance
“…In some cases, two MCAs arise from the ICA, such as accessory MCA or duplicated MCA. 24) In MCA fenestration, MCA originates as a single trunk, but there is a presence of a fenestration. 7) The term, duplicated origin of the MCA indicates an anomaly wherein, two MCA arise separately from the terminal segment of ICA and fuse to form an arterial ring.…”
Section: Anomalies Of the Mcamentioning
confidence: 99%
“…In some cases, two MCAs arise from the ICA, such as accessory MCA or duplicated MCA. 24) In MCA fenestration, MCA originates as a single trunk, but there is a presence of a fenestration. 7) The term, duplicated origin of the MCA indicates an anomaly wherein, two MCA arise separately from the terminal segment of ICA and fuse to form an arterial ring.…”
Section: Anomalies Of the Mcamentioning
confidence: 99%
“…Although some reports have affirmed that the DMCA is a pure cortical vessel without perforating arteries,22 other authors have reported that the DMCA and the main MCA have perforating arteries to the anterior perforated substance 3. The DMCA had perforating arteries in three of four cases studied by Komiyama et al , while the main MCA had perforating arteries in all four cases 3 , 20…”
Section: Discussionmentioning
confidence: 98%
“…Abanou et al reported that the DMCA and the accessory MCA that originates near the anterior communicating artery provide cortical supplies to the orbito-frontal area, and sometimes to the anterior temporal area 22. Gibo et al described a patient who had both a duplicated and an accessory MCA in which the duplicated artery was distributed to the temporopolar, anterior, and middle temporal areas 23.…”
Section: Discussionmentioning
confidence: 99%
“…10] Aus der einzigen Trifurkation der A. carotis interna unseres Untersuchungsgutes entsprangen die A. cerebri anterior und 2 Stämme der MCA. Vom Versorgungsge biet ausgehend, handelt es sich dabei nicht um eine Arteria cerebri media accessoria, die ja nur die laterale orbitale Fläche des Frontallappens versorgt [7,26,27], sondern nach der Beschreibung von Teal et al [28] und Gibo et al [9] um eine Verdoppelung der MCA (Abb.4). Derartige Duplikationen wurden schon früher von Longo [29] und Adachi [30] als ausserordentliche Sonderfälle beschrie ben.…”
Section: Abb 2 Facies Superoiateralis Hemispherii Kortikale äSte Nachunclassified